2016
DOI: 10.1038/srep39702
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide - cysteine cycle system enhances cadmium tolerance through alleviating cadmium-induced oxidative stress and ion toxicity in Arabidopsis roots

Abstract: Cadmium (Cd 2+ ) is a common toxic heavy metal ion. We investigated the roles of hydrogen sulfide (H 2 S) and cysteine (Cys) in plant responses to Cd 2+ stress. The expression of H 2 S synthetic genes LCD and DES1 were induced by Cd 2+ within 3 h, and endogenous H 2 S was then rapidly released. H 2 S promoted the expression of Cys synthesis-related genes SAT1 and OASA1, which led to endogenous Cys accumulation. The H 2 S and Cys cycle system was stimulated by Cd 2+ stress, and it maintained high levels in plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(60 citation statements)
references
References 54 publications
0
59
1
Order By: Relevance
“…This study was carried out on Arabidopsis (Arabidopsis thaliana), including Col-0 wild type and lcd (SALK_082099), des1-1 (SALK_103855), lcddes1-1 (lcd and des1 cross), and oasa1 (SALK_074242c) mutants (Jia et al, 2016). For the overexpressing lines, OE LCD and OE DCDES, the LCD and DCDES fragments were amplified from total cDNA and cloned into the pCAMBIA1300-35S vector with the restriction sites XbaI and KpnI.…”
Section: Plant Materials and Chemical Treatmentsmentioning
confidence: 99%
“…This study was carried out on Arabidopsis (Arabidopsis thaliana), including Col-0 wild type and lcd (SALK_082099), des1-1 (SALK_103855), lcddes1-1 (lcd and des1 cross), and oasa1 (SALK_074242c) mutants (Jia et al, 2016). For the overexpressing lines, OE LCD and OE DCDES, the LCD and DCDES fragments were amplified from total cDNA and cloned into the pCAMBIA1300-35S vector with the restriction sites XbaI and KpnI.…”
Section: Plant Materials and Chemical Treatmentsmentioning
confidence: 99%
“…H 2 S alleviates Cd toxicity in plants. Exogenous H 2 S recovered Cd-induced growth inhibition in Brassica napus, Arabidopsis, and barley [25][26][27]. 70 µM H 2 S largely stimulated proliferation of T. thermophila (Fig.…”
Section: H 2 S Mitigates Inhibition Of Proliferation Of T Thermophilmentioning
confidence: 89%
“…It is well known that antioxidant defense system increases organism tolerance against metal-induced toxicity by upregulating the nonenzymatic antioxidants and different antioxidant enzymes. H 2 S increase GSH content and antioxidant enzymes activity in Arabidopsis [26]. Under Cd stress, GSH content increased by 51% and exogenous H 2 S supplement further increased the GSH content in T.…”
Section: H 2 S Alleviates Lipid Peroxidation and Improves Antioxidantmentioning
confidence: 90%
“…Their toxicity also affects the levels of sulfane sulfur-containing compounds ( Table 4, Figure S1 Supporting information), which in case of the enhanced ROS generation may show their antioxidative properties [11]. Jia et al [55] suggested that the H 2 S and Cys cycle system is a key regulator of the response to cadmium-stress in plants that acts to induce and maintain levels of bioactive molecules (H 2 S, Cys, GSH and MTs) that improve plant resistance to cadmium-stress. Our results confirmed some of the results by Jia et al [55], namely, that the CTH gene expression up-regulation results in the elevated Cys level in the liver (Tables 4 and 5), Similarly, the MPST gene expression up-regulation results in the elevated Cys and GSH levels (Tables 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…Jia et al [55] suggested that the H 2 S and Cys cycle system is a key regulator of the response to cadmium-stress in plants that acts to induce and maintain levels of bioactive molecules (H 2 S, Cys, GSH and MTs) that improve plant resistance to cadmium-stress. Our results confirmed some of the results by Jia et al [55], namely, that the CTH gene expression up-regulation results in the elevated Cys level in the liver (Tables 4 and 5), Similarly, the MPST gene expression up-regulation results in the elevated Cys and GSH levels (Tables 4 and 5). The present report is the first to widely describe the role of the sulfane sulfur/H 2 S generating enzymes and the Cys/glutathione system in Pb 2+ , Hg 2+ and Cd 2+ stress, in various frog tissues, and to explore the mechanisms mediating heavy metal related stress.…”
Section: Discussionmentioning
confidence: 99%